Implementasi Program Kampus Berdampak Melalui Edukasi Sampah Dan Gotong Royong Lingkungan Masyarakat - Basar Al Mustaqim Mustaqim; Astianza Ramadhani; Nessa Lendrawati; Irlan Ulama Lase; Fiska Ariska; M Akrom Sayuti; Ondihon Ady Prima Pasaribu; Royan Fathona; Riefky Aditya; Lidya Nataliya; Seno Pratomo; Feby Elra Perdima; Liza Yulianti (Jurnal Karya Nyata Pengabdian, 2026)
The Impactful Campus Program (Kampus Berdampak) is an implementation of the role of higher education institutions in community service aimed at addressing social and environmental issues. One of the environmental problems commonly found in communities is inadequate waste management and low collective awareness of environmental cleanliness. This program was conducted in RT 12 RW 03, Sawah Lebar Subdistrict, with the aim of increasing community knowledge, awareness, and participation in waste management through environmental education and mutual cooperation activities. The implementation methods included educational sessions on household waste sorting and management, interactive discussions, and collective environmental clean-up activities. The results showed an improvement in the community’s understanding of proper waste management and the growth of collective awareness and cooperation in maintaining environmental cleanliness. The Impactful Campus Program is expected to serve as an initial step in fostering sustainable environmentally friendly behavior and strengthening collaboration between universities and local communities.